Effectiveness of inspiratory muscle training in patients with a chronic respiratory disease: an overview of systematic reviews - Torres-Castro, Rodrigo; Caicedo-Trujillo, Saul; Gimeno-Santos, Elena; Gutiérrez-Arias, Ruvistay; Alsina-Restoy, Xavier; Vasconcello-Castillo, Luis; Seron, Pamela; Spruit, Martijn A.; Blanco, Isabel; Vilaró, Jordi (Frontiers in Sports and Active Living, 2025)
IntroductionThere has been inconclusive findings regarding the effectiveness of inspiratory muscle training (IMT) in chronic respiratory diseases (CRDs). Our objective was to determine the effectiveness of IMT on exercise tolerance, maximum respiratory pressure, lung function, symptoms and quality of life in different CRDs.MethodsWe conducted an overview of systematic reviews (SRs) in adults with CRDs who underwent IMT. We reviewed five databases in March 2025. We chose the most comprehensive SRs to report on the analysed outcomes.ResultsTwenty-three SRs were included. In chronic obstructive pulmonary disease (COPD), IMT increased the six-minute walk distance (6MWD) by 35.7 m (95% CI 25.7, 45.7), maximum inspiratory pressure (MIP) by 10.9 cmH2O (95% CI 8.0, 13.9). In asthma, IMT increased the forced expiratory volume in the first second (FEV1) by 3.3%pred (95% CI 1.4, 5.1), forced vital capacity (FVC) by 4.1%pred (95% CI 1.0, 7.3), MIP by 21.9 cmH2O (95% CI 15.0, 28.8), and dyspnoea was reduced (standard mean difference −0.8, 95% CI −1.3,−0.2). In obstructive sleep apnoea (OSA), IMT increased MIP by 29.6 cmH2O (95% CI 6.0, 53.1). In pulmonary hypertension (PH), IMT increased 6MWD by 39.0 m (95% CI 20.7, 57.4), MIP in 21.2 cmH2O (95% CI 11.3, 31.1), maximum expiratory pressure by 14.4 cmH2O (95% CI 6.9, 21.9), and dyspnoea was reduced by 0.5 (95% CI 0.1, 0.9) in modified Medical Research Council scale. In lung resection (LR), IMT increased MIP by 8.1 cmH2O (95% CI 1.3, 14.9). In bronchiectasis, IMT increased MIP by 6.1 cmH2O (95% CI 1.4, 10.8). Overall, the most consistent effect of IMT across different CRDs was an increase in MIP.ConclusionIMT improved several clinically relevant outcomes, including MIP, exercise capacity, and dyspnoea in different CRDs. However, the limited evidence for certain outcomes and populations highlights the need for further high-quality studies.